Unvoiced Trauma: Narrative Silence and Ethical Boundaries in The Silent Patient - Tawhida Akhter (International Journal of Linguistics, Literature and Translation, 2025)
This paper explores the complex ethical dilemmas faced by psychotherapists in The Silent Patient by Alex Michaelides 2019. Through the lens of the novel's protagonist, Theo Faber, the paper delves into the blurred lines between therapeutic boundaries and personal involvement. It examines the ethical implications of a therapist developing a personal connection with a patient, particularly when that patient is a suspected murderer. The paper also discusses the power imbalance inherent in the therapeutic relationship and the potential for exploitation. By analyzing these themes, the paper aims to raise questions about the ethical responsibilities of mental health professionals and the challenges they may encounter in maintaining professional boundaries. The novel explores the tension between the desire to help a patient and ethical obligations of a healthcare professional. It leads the readers to consider the potential consequences of violating ethical codes. The novel raises questions about the patient and the therapist boundaries and the rule of ethics in the novel. The paper also discusses the power imbalance inherent in the therapeutic relationship and the potential for exploitation. By analysing these themes, the paper aims to raise questions about the ethical responsibilities of mental health and crossing lines between professional and personal involvement.